More than a prophet : an insider's response to Muslim beliefs about Jesus and Christianity - Caner, Emir Fethi; Caner, Ergun Mehmet (Grand Rapids : Kregel Publications, 2003)
For the world's one billion Muslims, Jesus is a prophet. A highly respected prophet, but one of many throughout history. For Christians, Jesus is more than a prophet. He alone is God incarnate, Lord and Savior. And therein lies the most profound difference between the two faiths. Based upon the authors' extensive dialogues and debates with skeptical, angry, and interested Muslims, liberal Christians, and mainstream journalists, More Than a Prophet answers nearly 150 questions about Islamic and Christian faith. Sympathetic to Muslim concerns yet uncompromising in its portrayal of historic Christian truth, More Than a Prophet is an indispensable handbook for Christians who want to share their faith with sensitivity and intellectual honesty. It is also a helpful introductory resource for those seeking to understand Jesus. - Back cover.
Questions Concerning the Name and Nature of God -- Questions Concerning the Nature of Jesus Christ (Isa) -- Questions Concerning the Nature of the Qur'an and the Bible -- Questions Concerning the Old Testament -- Questions Concerning the New Testament -- Questions Concerning the Atonement and Salvation -- Questions Concerning Eschatology (End Times) -- Questions Concerning Ethics and Politics -- Questions Concerning Culture and Pluralism -- Questions Concerning Religious Liberty -- Questions Concerning World History -- Questions Concerning Controversy and Jihad.
Includes bibliographical references.
Keywords: Islam -- Controversial literature; Jesus Christ -- Islamic interpretations; Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Jesus Christ; Christianity; Interfaith relations; Islam; Islamic interpretations of Jesus Christ; Controversial literature